2023
DOI: 10.1111/bju.16127
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age >70 years on oncological outcomes in patients with non‐muscle‐invasive bladder cancer treated with Bacillus Calmette–Guérin

Abstract: ObjectiveTo evaluate the impact of age on oncological outcomes in a large contemporary cohort of patients with non‐muscle‐invasive bladder cancer (NMIBC) treated with adequate Bacillus Calmette–Guérin (BCG).Patients and MethodsWe performed an Institutional Review Board‐approved retrospective study analysing patients with NMIBC treated with adequate BCG at our institution from 2000 to 2020. Adequate BCG was defined as per United States Food and Drug Administration (FDA) guidelines as being receipt of at least f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The current EAU risk classification systems incorporate some parameters that are controversial such as tumour size, whose estimation is often inaccurate, and age >70 years [5,18]. We also observed a significant association between E/M infiltration of the LP and the presence of histological subtypes and LVI.…”
Section: Discussionmentioning
confidence: 52%
“…The current EAU risk classification systems incorporate some parameters that are controversial such as tumour size, whose estimation is often inaccurate, and age >70 years [5,18]. We also observed a significant association between E/M infiltration of the LP and the presence of histological subtypes and LVI.…”
Section: Discussionmentioning
confidence: 52%
“…Notably, recently, it has been found that, in a cohort of patients with NMIBC treated with adequate BCG, age >70 years was not a predictor of poor outcomes or associated with adverse oncological events. BCG should not be withheld from older patients seeking bladder-sparing options [171]. In addition to triggering innate and adaptive immunity, BCG exerts direct cytotoxic effects on BC cells, activating apoptosis through the caspase 8, caspase 9, and proapoptotic protein BID signaling pathway [172,173].…”
Section: Microbiome and Bcg Responsivenessmentioning
confidence: 99%
“…Tumor characteristics (at first TURB) consisted of stage (pTa low-grade (LG) vs. pTa high-grade (HG) vs. pT1 vs. pTis), EAU risk groups (version 2020; low vs. intermediate vs. high vs. very high) [16], concomitant carcinoma in situ (CIS), presence of the detrusor muscle in histology, and adjuvant therapy (either immediate postoperative intravesical chemotherapy or Bacillus Calmette-Guérin (BCG)). The covariates were chosen based on their recognized associations with the outcomes of NMIBC patients [16,[18][19][20][21][22]. The endpoint of the study was a recurrence of primary NMIBC.…”
Section: Variables Of Interest and Outcomesmentioning
confidence: 99%